Disruptions to the social determinants of health and mental health indicators during the pandemic in eight countries - Salma M. Abdalla; Samuel B. Rosenberg; Gregory H. Cohen; Catherine K. Ettman; Laura Magana; Elaine O. Nsoesie; Lora L. Sabin; Sandro Galea (SSM - Mental Health, 2023)
Introduction: The social determinants of health (SDoH) shape both the risk of mental disorders and access to treatment. There is ample evidence detailing the decline in mental health during the Covid-19 pandemic. However, there is a gap in our understanding of the association between disruptions to SDoH and adverse psychological indicators in different contexts. Methods: Data were collected through a multi-country, random, anonymous, opt-in, cross-sectional online survey in eight geographically diverse countries—Brazil, China, Germany, Egypt, India, Indonesia, Nigeria, and the United States. We documented the relationship between experiencing self/family job loss, financial problems, and food/supplies shortages and adverse mental health indicators—depression symptoms and probable posttraumatic stress disorder (PTSD). Results: Almost one-third of respondents who experienced at least one disruption had depression symptoms (32.3%, 95% CI: 30.3%–34.4%). This was consistent across countries, except Indonesia. Reporting at least one Covid-19 related SDoH disruption had 1.26 (95% CI: 1.14-1.39) times the risk of depression symptoms compared to respondents reporting no Covid-19 related SDoH disruptions. Across countries, experiencing at least one Covid-19 related SDoH disruption had significantly increased risk of depression symptoms, except for China, Egypt, and Indonesia. The prevalence of probable PTSD among respondents who reported at least one SDoH disruption was 8.4% (95% CI: 7.3%–9.5%). The prevalence was comparably elevated within countries, except for China. Reporting at least one SDoH disruption was associated with greater odds of probable PTSD in the overall adjusted model (OR=2.87, 95% CI: 2.31-3.59) and in the models for countries except for China and Indonesia. Conclusion: Disruptions to SDoH due to the pandemic were associated with an elevated burden of symptoms of depression and probable PTSD across geographically diverse countries, with a few exceptions particularly in China. This highlights the need to account for the broader consequences of mitigation policies that potentially have an impact on the health of populations.